Cultural-Cognitive Analysis of Aphorisms Expressing the National Picture of the World (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Aphorisms are linguistic condensations of cultural experience and collective wisdom that encode the cognitive and axiological orientations of a nation. This study investigates how aphorisms reflect and shape the national picture of the world through cultural-cognitive mechanisms. Drawing on cognitive linguistic and cultural linguistics frameworks, the paper explores the ways in which English and Uzbek aphorisms express worldviews, values, and conceptual metaphors unique to their speech communities. The findings demonstrate that aphorisms serve as a linguistic mirror of national mentality, representing how people conceptualize reality, time, morality, and human relationships.